Landfill gas to energy plant with intergrated VOCS removal system and modified organic rankine cycle as waste heat recovery system a plant design - Garcia, Felipe D. Jr.; Quezon, Frances Abegail G.; Dela Cruz, John Von Wernher C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The endless demand for energy, coupled with the gradual deterioration of the environment, has led to the emergence of utilization of renewable energy sources. One of these renewable energy sources was landfill gas whose main component, methane, can be combusted to generate electricity. The proposed plant location was in Mindanao (Metro Cagayan de Oro) to reduce dependence on less reliable source of energy. A new landfill was supposed to be constructed in the area as well, which would be utilized by the proposed plant. The proposed plant was divided into three parts: landfill gas capture and treatment, combustion, and an organic rankine cycle for waste heat recovery. Treatment of landfill gas was vital in order to meet the emission limits of VOCs. Meanwhile, the organic rankine cycle was employed in order to recover waste heat as well as reduce emitted thermal pollution. The first part of the plant was composed of a blower, and absorption tank, and an adsorption tank. Meanwhile, the second part was composed of a compressor, turbine, and combustion chamber. Finally, the third section of the plant consisted of heat exchangers, pumps, turbines, and a heater. Stainless steel piping was implemented in the plant and flow, concentration, pressure, and temperature analyzers were used as necessary. At 80 %, 75 % and 60 % landfill gas capture efficiencies respectively, the maximum power generated would be 1.82MW, 1.71MW, and 1.39MW. This was based on the assumption that the plant will operate for 23 years before finally shutting down because of the declining raw material provided by the landfill. In the technical aspect, the cost driver for equipment acquisition expenses was the compressor. All rotating equipment were also designed to operate with a reliability unit to take into account equipment maintenance. Two adsorption towers would also be present on-site to allow for continuous plant operations during change of adsorption beds. To validate the establishment of our landfill gas-to-energy plant, its economic feasibility was studied. The profitability analysis of our proposed plant revealed that at 5 % bank interest, IRRs of 9 %, 8 %, and 7 % were obtained for 80 %, 75 %, and 60 % landfill gas capture efficiencies, respectively. Such a trend implies that investing in the landfill gas-to-energy plant was more profitable compared to investing in a bank. Aside from this. payback and positive cash flows were observed earlier in landfills operating at higher landfill gas capture efficiencies. Lastly, the sensitivity analysis showed that payback has the strongest dependence on sales as compared to fixed capital investment and cost of goods sold, whereas the break-even analysis showed that break-even analysis showed that the break-even point occurred at approximately 0.08 MW.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Landfill gases; Energy conversion; Gas power plants -- Design and construction